Urban Redevelopment and Traffic Congestion Management Strategies - Wang, Yanli; Wu, Bing.; Li, Linbo (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book focuses on the relationship between urban land redevelopment and traffic systems and discusses the related research. Consisting of three main parts, the first analyzes the interaction between land redevelopment and traffic congestion as well as the mechanisms and causes of traffic congestion. The second part presents strategies for the prevention and control of traffic congestion under urban land redevelopment, proposing a two-stage evaluation system of traffic congestion pre-inspection and traffic impact analysis in the planning and implementation stages of land redevelopment. Lastly, the third section includes an application case analysis of the proposed traffic congestion management strategy.
Preface -- Introduction -- The mechanism of traffic congestion under land redevelopment -- The traffic congestion control strategy framework for land redevelopment -- Traffic demand analysis model for land redevelopment -- Pre-inspection of traffic congestion during planning stage of land redevelopment -- The traffic impact analysis during implementation stage of land redevelopment -- The application of land redevelopment and traffic congestion control strategy.
Keywords: Human geography; Sociology, Urban; Urban policy; Human Geography; Urban Sociology; Urban Policy